Identifying Student Perceptions of Different Instantiations of Open Pedagogy - Hilton, John; Hilton, Bryson; Ikahihifo, Tarah K.; Chaffee, Reta; Darrow, Jennifer; Guilmett, JoAnn; Wiley, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
As the adoption of open educational resources (OER) continues to increase, instructors have started using these resources for more than simply delivering content. Open pedagogy is a term used to describe a range of instructional practices that often incorporate OER into the learning process. This study examined student perceptions of two approaches to open pedagogy—student creation of multiple-choice questions and student creation of the syllabus and corresponding course assignments. The sample included responses from 84 students at two colleges in the United States. Results showed that students who created the syllabus and assignments had a more positive experience and were more likely to enroll in a future course that implements this strategy. Those in the multiple-choice course felt that the approach was less conducive to learning than traditional learning activities. The significant differences in student feedback on two different approaches, both of which could be termed open pedagogy, indicate that more research is needed to examine the efficacy of the wide variety of approaches to open pedagogy. Moreover, the perceived efficacy of one instantiation of open pedagogy does not equal the effectiveness of open pedagogy, broadly defined.